Formalization of relationship management (interactions) in a virtual company (Путеводитель предпринимателя, 2020)
In the article presents the formalization of relationship management (interactions) in a virtual company through the classification of its human resources and their separation conditional on smart nodes of several types. Considers the problems interaction between smart nodes, as well as the function of each node in intellectual isolation.